Teamwork Dynamics and Organizational Behavior in Islamic Educational Institutions: Toward a Value-Embedded Conceptual Framework - Fadhilla Fadhilla; Agung Safitri; Yusuf Effendi; Nirva Diana; Eti Hadiati; Majid M.H.M (Maharot : Journal of Islamic Education, 2026)
This integrative literature review develops the Value-Embedded Teamwork Effectiveness Framework (VETEF) for Islamic educational institutions. Drawing on 50 peer-reviewed journal articles and two foundational monographs on team effectiveness, teacher collaboration, leadership, organizational culture, and Islamic work ethic, the review synthesizes how structural conditions, leadership practices, team processes, and Islamic ethical values jointly shape collaborative performance. The analysis identifies four interdependent domains: (a) structural enablers, including role clarity, adequate resources, team composition, training, and recognition; (b) leadership enablers, including shared vision, participative decision-making, conflict regulation, and external coordination; (c) team processes, including information sharing, psychological safety, shared cognition, and mutual accountability; and (d) Islamic ethical mechanisms, particularly amanah, shura, ukhuwwah, ihsan, and adl. Rather than treating Islamic values as supplementary moral discourse, the framework positions them as context-specific mechanisms that reinforce trust, dialogue, commitment, and responsible collective action. The review also shows that team effectiveness should be evaluated through multiple outcomes, including team learning, instructional and service quality, innovation, teacher commitment, and sustainable institutional performance. This article contributes to the literature by moving beyond descriptive accounts of collaboration and proposing a theoretically integrated model that can guide leadership practice and future empirical testing in madrasahs, pesantren, and other Islamic educational organizations.